DEVELOPMENT OF A LAND DEGRADATION ASSESSMENT MODEL BASED ON FIELD INDICATORS ASSESSMENT AND PREDICTION METHODS IN WAI SARI, SUB-WATERSHED KAIRATU DISTRICT, WESTERN SERAM REGENCY, MALUKU PROVINCE, INDONESIA - Silwanus M. Talakua; Rafael M. Osok (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
The study was conducted in Wai Sari sub-watershed, Western Seram Regency Maluku to develop an accurate land degradation assessment model for tropical small islands. The Stocking’s field land degradation measurement and RUSLE methods were applied to estimate soil loss by erosion and the results of both methods were statistically tested in order to obtain a correction factor. Field indicators and prediction data were measured on 95 slope units derived from the topographic map. The rates of soil loss were calculated according to both methods, and the results were used to classify the degree of land degradation. The results show that the degree of land degradation based on the field assessment ranges from none-slight (4.04 - 17.565 t/ha/yr) to very high (235.44 - 404.00 t/ha/yr), while the RUSLE method ranges from none-slight (0.04-4.59 t/ha/yr) to very high 203.90 - 518.13 t/ha/yr. However, the RUSLE method shows much higher in average soil loss (133.4 t/ha/yr) than the field assessment (33.9 t/ha/yr). The best regression equation of logD/RP = - 0.594 + 1.0 logK + 1.0 logLS + 1.0 logC or D = 0.2547xRxKxLSx CxP was found to be a more suitable land degradation assessment model for a small-scale catchment area in the tropical small islands.